Analysis of Major Financial Audit Scandals and Their Impact on Regulatory Change - Simonaitytė, Živilė (Buhalterinės apskaitos teorija ir praktika, 2024)
The first company collapse followed by an auditor misconduct scandal occurred in 1925. Since then, until the global economic crisis (2009), similar cases have led to changes in audit regulation and clearer or stricter responsibilities for auditors. Recently, however, the regulatory framework has not changed in the face of new audit scandals. The aim of this paper is to analyse audit scandals and their impact on audit regulation. In order to identify the changes in audit regulation as a result of financial audit scandals and the recent trends in audit regulation, the article analyses the oldest and most significant audit scandals that have led to regulatory changes, the impact of financial audit scandals in companies operating in different countries around the world, and reviews the major financial audit scandals in Lithuania. The analysis of literature, financial, court decisions and regulatory legislation identifies the oldest financial audit scandals in history, identifies the scandals that have led to regulatory changes, and examines the largest regional and national scandals and their impact on regulatory changes.